2022
DOI: 10.1029/2021tc006728
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Oblique Inversion: A Case Study From the Cretaceous Fold and Thrust Belt of the Western Transdanubian Range (TR), West Hungary

Abstract: Inversion of pre‐existing normal faults is a frequent phenomenon in orogenic belts. However, their impact on the evolution of the Cretaceous Eoalpine orogeny is poorly studied, despite the widespread presence of Triassic and Jurassic normal faults. Our study area is the SW part of the Transdanubian Range (TR), which represents the uppermost thick‐skinned nappe of the Eoalpine orogeny in the Alpine realm. The variable trend of Cretaceous contractional structures within the Transdanubian Range has been tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…1b), which is traditionally explained by two or even three phases of folding and thrusting in the TR, well separated in time and in tectonic context (Tari, 1994;Csontos and Vörös, 2004;Csontos et al, 2005;Pocsai and Csontos, 2006;Palotai et al, 2006;Sasvári, 2008Sasvári, , 2009Tari and Horváth, 2010;Fodor et al, 2018;Szives et al, 2018). In contrast, our early results suggested that deviations of fold trends can be explained rather by inheritance of Triassic and Jurassic pre-orogenic normal faults than by multiphase folding (Héja et al, 2016(Héja et al, , 2017(Héja et al, , 2022. In this work, we document outcrop-scale structures and faults-slip analysis which serve as the basis of this alternative explanation for the number and character of folding phases.…”
Section: Central European Geologymentioning
confidence: 66%
See 3 more Smart Citations
“…1b), which is traditionally explained by two or even three phases of folding and thrusting in the TR, well separated in time and in tectonic context (Tari, 1994;Csontos and Vörös, 2004;Csontos et al, 2005;Pocsai and Csontos, 2006;Palotai et al, 2006;Sasvári, 2008Sasvári, , 2009Tari and Horváth, 2010;Fodor et al, 2018;Szives et al, 2018). In contrast, our early results suggested that deviations of fold trends can be explained rather by inheritance of Triassic and Jurassic pre-orogenic normal faults than by multiphase folding (Héja et al, 2016(Héja et al, , 2017(Héja et al, , 2022. In this work, we document outcrop-scale structures and faults-slip analysis which serve as the basis of this alternative explanation for the number and character of folding phases.…”
Section: Central European Geologymentioning
confidence: 66%
“…In a recent paper, Héja et al (2022) give an alternative interpretation for the three generation of folds in the KH. This concept (third scenario, Fig.…”
Section: Cretaceous -Early Miocene (?) Contractional Deformations -D3...mentioning
confidence: 99%
See 2 more Smart Citations
“…Shortening of passive continental margins is typically associated with the reactivation of inherited normal faults, inversion of sedimentary basins, and their incorporation in fold-and thrust belts (e.g., Turner and Williams, 2004;Cooper and Warren, 2020). Inverted sedimentary basins are known from numerous orogenic settings worldwide, from, e.g., the European Alps (Boutoux et al, 2014;Gillcrist et al, 2015;Granado et al, 2016;Oswald et al, 2018;Héja et al, 2022), the Apennines (Scisciani et al, 2001;Pace et al, 2014), the Pyrenees (Tavani et al, 2011;Mencos et al, 2015), Iberia (Ramos et al, 2017), the Atlas Mountains of Morocco (Beauchamp et al, 1999) and Algeria (Bracène and Froizon De Lamotte, 2002), and from the South American Andes (Kley and Monaldi, 2002;Giambiagi et al, 2003;Kley et al, 2005;Carrera et al, 2006). For understanding complex and large-scale 3D tectonic patterns resulting from superposed extension and compression phases, tectonic inversion was already long studied through analogue (e.g., Buchanan and Mcclay, 1991;Sassi et al, 1993;Brun and Nalpas, 1996;Amiliba et al, 2005;Panien et al, 2005;Mattioni et al, 2007;Yagupsky et al, 2008;Cerca et al, 2010;Yamada and Mcclay, 2010;Bonini et al, 2012;Di Domenica et al, 2014;Granado et al, 2017;Deng et al, 2020;Zwaan et al, 2022) and numerical (Buiter et al, 2006;Panien et al, 2006;Buiter et al, 2009;Granado and ...…”
Section: Introductionmentioning
confidence: 99%